Gelation of an Organically Crosslinked PHPA Polymer Gel System: An Experimental Study - Vaishnav, M.; Verma, N. K. (Journal of Scientific Research, 2023)
Excessive water production in the oil field is the major difficulty in production for the petroleum industry. Remedial techniques need to be applied to control this excess water production considering the health, safety, and environmental issues and improve the reservoir's economic and productive life. In this study polymer gel system comprising the polymer partially hydrolyzed polyacrylamide (PHPA) and organic cross-linkers (Hydroquinone and Hexamethylene tetramine) were prepared as a water shut-off system to control the excessive production of water in the oil field. The effect of various parameters such as temperature, pH, cross-linker concentration, degree of hydrolysis, and divalent cations on gelation time was investigated using the bottle testing method. The importance of retarders at high temperatures was also evaluated. The gelation temperature was varied from 90 °C to 120 °C to study the effect of different parameters on the gelation time and gel behavior. This study suggests that Partially Hydrolyzed Polyacrylamide (PHPA) with organic cross-linkers can be an effective polymer gel system for water shut-off operations, and with the addition of retarders at high temperature to control gelation time, the performance of the gel can be improved.